Inertial measurements of curling stone movement - Dzikowski, B.; Pachwicewicz, M.; Weremczuk, J. (International Scientific Conference on Optoelectronic and Electronic Sensors, 2018)
Curling is a winter Olympic sport, in which athletes slide 20-kilogram granite stones on the surface of ice to the target called "house". An inertial measurement unit was attached to a curling stone handle in order to measure acceleration and rotation during a delivery. In this paper, we present the measurement system that consisted of accelerometers and a gyroscope as well as the results. Obtained results show that the movement of a curling stone has a high-frequency noise-like nature, which is likely to be caused by the stick-slip mechanism between the granite stone and the pebbled ice surface.